(untitled) (IAHS Medical Journal, 2022)
Background : To asses resident”s performance of phacoemulsification surgery and determine which steps of the procedure are most difficult to learn and to measure rate of intraoperative complications. Materials and methods : A prospective study was carried out at Bangladesh Eye Hospital between January 2016 to December 2017. The total 50 (Fifty) eyes of fifty patients diagnosed cataract patient were selected randomly. Results : Corrected visual outcome after 3 weeks of operation were 6/6 in 18 patients (36%) 6/9 in 17 pts (34%) 6/12 in 7 pts (14%) 6/18 in 4 pts (8%) 6/24 in 3 (6%) and 6/36 in one pt (2%). Overall intraoperative complications occurred in 14 cases (28%) including with cases experiencing more than one complication. There is corneal wound burn 2 cases (4%) Iris catch by phaco probe 3 cases (6%) Anterior capsular edges tear 3 cases (6%) Posterior capsular rupture 4 cases (8%) with vitrous loss 2 cases (4%) retained lens fragments 2 cases (4%). Post operative complications include wound gap, shallow anterior chamber, corneal stromal oedema and bullous keratopathy. Conclusion : The study indicates that a trainee can be taught phacoemulsification with acceptable complication rates and visual results. The results compare favourably with reports of senior surgeons converting to phacoemulsification, trainee surgeons learning extracapsular surgery, and recently reported phacoemulsification series. IAHS Medical Journal Vol 4(1), June 2021; 43-46